Sebaran Lokasi Kantor Kelurahan Di Kota Surabaya Timur Dengan Sistem Informasi Geografis (SIG) - Syah, Enggar Firman (Jurnal Vokasi Teknik Sipil, 2023)
The village office is a facility provided by the Surabaya City Government where the existence of the village office has the function of improving community services, carrying out government functions, and community empowerment to accelerate the realization of community welfare. Therefore, information regarding location mapping and distribution patterns of village offices can be communicated to the public using Geographic Information System (GIS) technology. It is hoped that even people who don't know will find it easier to find the location of the village office. In addition, the results of the mapping will reveal the pattern of distribution of village offices in East Surabaya and it is hoped that this research can become reference data for the government in the even distribution of village office locations in East Surabaya. This study uses the nearest neighbor analysis method with ArcGIS 10.8 software to determine the distribution pattern of village offices in East Surabaya. The results of this study are that the distribution pattern of village offices in East Surabaya shows a dispersed pattern and the range of services from village offices can be categorized as high with a distance of 3 km.